PREVENTION OF LOW BACK PAIN COMPLAINTS TO STUDENTS DURING ONLINE LEARNING IN THE TIME OF THE COVID-19 PANDEMIC - Indri Seta Septadina; Wardiansyah Wardiansyah; Msy Rulan Adnindya; Tri Suciati (Conferences of Medical Sciences Dies Natalis, 2021)
Low back pain is a widespread health problem worldwide and the leading cause of disability. Low back pain or lower back pain is a Musculoskeletal disorder caused by strenuous physical activity, and It causes muscle spasms and back stiffness. This complaint occurs because the muscles receive pressure due to workload continuously without getting relaxation opportunities. The incidence of low back pain in the world each year varies wildly, reaching 15 - 45%. According to WHO (2013), shows that 33% of the population in persistent pain develops. Data for LBP sufferers in Indonesia is unknown but is estimated to vary between 7.6% to 37% of the total population. LBP is not caused by organic disorders but by the wrong body position at work. With the issuance of a work from home policy for workers and online at students and students, there is a shift in low back pain at a young age. Low back pain continues to increase 5% every year. The intensity of physical movement, work and study so that laptops and smartphones are increasing. The increase in the duration of media use causes various kinds of effects, including influencing how students and workers learn.